Influence of the exercise frequency, intensity, time and type according to different training modalities on the cardiac rehabilitation programs - José Manuel Sarabia; Agustín Manresa-Rocamora; José Oliveira; Manuel Moya-Ramón (Asociación Española de Ciencias del Deporte, 2018)
Exercise-based cardiac rehabilitation is considered as a cornerstone of non-pharmacological treatments in cardiac patients and several previous studies have been performed with this population to know the effects of this treatment. The main goal of these researches has been to analyse the influence of different training modalities, such as endurance training, resistance training or combined endurance and resistance training. Within endurance training, the principal topic is the efficacy of moderate continuous training and high-intensity interval training. However, the findings of these previous studies are controversial and a very high heterogeneity has been reported in previous meta-analyses. Despite the fact that the influence of the training variables, such as frequency, intensity, time and type (FITT variables) has been widely reported, none of the previous studies have considered these variables globally in order to explain the controversial results. Therefore, the aim of this review was to interpret previous studies to explain this heterogeneity and set out proposals to manage exercise-based cardiac rehabilitation properly. The review helped to show the lack of control of FITT variables and their influence in the effect of exercise-based cardiac rehabilitation, highlighting the need to control these variables properly to reach higher adaptations in cardiac rehabilitation.